QT INTERVALS IN ATHLETES. Issue 17 (24th October 2013) - Milne, CJ; Stewart, K; Hillis, WS
Abstract : Aim: To determine factors affecting the QT interval in athletes and find an improved means of QT correction (QTc) Method: Data was gathered from the CAYA (Cardiovascular Assessment in Young Athletes) screening programme for athletes aged 35 and under. This included assessment of personal/family history, clinical examination, ECG and echocardiogram. This study used ECG data of heart rate, measured QT interval and Bazett 1 corrected QT interval (QTc). Athletes were divided into age groups and sex to provide age and sex related comparisons. Analysis was performed using co-efficients to determine significant factors affecting QTc. This was then added to linear regression models to provide a most accurate correlation of QT interval based on these factors. Results: Complete data was held for 1545 athletes (1280 males, 265 females) aged 10–35. Overall data showed a mean age of 18.03. Heart rate varied from 34–123 bpm. Bazett QTc interval varied from 308–592 ms. Mean Bazett QTc of the males was 406.6 ms, and 422.5 ms. From the CAYA data, statistical significance was shown for the factors of age, sex and heart rate in determining QT interval. This provided the following conversion for most accurate determination of QT interval based on the statistically significant factors: QT=515.7–(1.984×HR)+(0.601×Age)+(9.33 if female) Conclusion: QT interval is dependent on heart rate, sex and age, and all factors should be taken into account when determining QTc. The above formula provides the most accurate means of determining a QT interval based on an athlete's individual details. However, further work is ongoing to determine a new formula for means of QT correction that also accounts for these factors, as Bazett's does not. This will then allow a fairer comparison between individual athletes.